The Influence Of Financial Literacy On The Financial Behavior Of Members Of The Osseda Faolala Women's Consumer Cooperative In Nias - Irwan Kristian Waruwu; Idarni Harefa; Maria Magdalena Bate'e; Tiarni Duha (Universitas Dehasen Bengkulu, 2026)
The Osseda Faolala Women's Consumer Cooperative in Nias has problems in the financial behavior of its members, which is based on poor financial literacy of its members. One of the problems in the cooperative's financial behavior is in the repayment of loan credit or bad credit. Problematic loans are burdens that have not been collected or loans that are not paid, doubtful because of difficulties in payment due to certain aspects. The purpose of this study is to determine whether there is an influence and how much influence the financial literacy of the Osseda Faolala Women's Consumer Cooperative in Nias has on the financial behavior of its members. The type of research used is quantitative research. Where the population is 110 people and the sampling technique used is probability sampling with simple random using the Slovin formula, a sample of 52 people was obtained. The results of this study indicate the influence of Financial Literacy (X) on the Financial Behavior (Y) of Members of the Osseda Faolala Women's Cooperative in Nias. This is indicated by the results of the data test on the influence of the variable Financial Literacy (X) on the Financial Behavior of Members of the Osseda Faolala Female Cooperative in Nias, obtained results with a mean T-count of 2.806> T-table 2.009 and a significant value of 0.001 <0.05, meaning the hypothesis is accepted, the Financial Literacy variable (X) partially has a positive and significant influence on the Financial Behavior (Y) of Members of the Osseda Faolala Female Cooperative in Nias. Based on the research that has been conducted, it is known that Financial Literacy (X) has an influence of 0.369 or if expressed as a percentage of 36.9% on the decision of guests to choose a hotel in the city of Gunungsitoli. While the other 63.1% is influenced by other factors.